Burden of Hypertension in Recently Diagnosed Type 2 Diabetes Mellitus - Sharma, SK; Karki, P; Shrestha, N; Dhakal, S; Gupta, PR; Ahmed, WS; Gupta, N; Badu, B; Rajbhandari, S (Nepalese Heart Journal, 2004)
Cardiovascular diseases are the major cause of death In diabetes patients. Many factors including hypertension contribute to the high prevalence of cardiovascular disease in diabetes.